2022
DOI: 10.3390/antibiotics11070904
|View full text |Cite
|
Sign up to set email alerts
|

Cefiderocol for Carbapenem-Resistant Bacteria: Handle with Care! A Review of the Real-World Evidence

Abstract: (1) Background: healthcare-associated infections are one of the most frequent adverse events in healthcare delivery worldwide. Several antibiotic resistance mechanisms have been developed, including those to carbapenemase. Cefiderocol (CFD) is a novel siderophore cephalosporin designed to treat carbapenem-resistant bacteria. (2) Methods: we performed a systematic review of all cases reported in the literature to outline the existing evidence. We evaluated real-world evidence studies of CFD in the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…While we could rely on the improved efficacy of other more current antibacterial agents [ 28 , 29 ] or maybe some natural substances [ 30 ] and their derivatives that are expected in our healthcare facilities, we cannot conclude that the resistance of CR K. pneumoniae strains will not increase over time.…”
Section: Discussionmentioning
confidence: 99%
“…While we could rely on the improved efficacy of other more current antibacterial agents [ 28 , 29 ] or maybe some natural substances [ 30 ] and their derivatives that are expected in our healthcare facilities, we cannot conclude that the resistance of CR K. pneumoniae strains will not increase over time.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world data on CEFID use for carbapenem-resistant pathogens have recently been published [ 59 ]. The authors reported on 172 individuals, including the CREDIBLE-CR patients.…”
Section: Recently Approved Antimicrobial Agentsmentioning
confidence: 99%
“…The authors reported on 172 individuals, including the CREDIBLE-CR patients. Many patients reported adverse events, such as diarrhea or fever, although only four discontinued treatment because of these events [ 59 ]. Finally, there is scarce and inconclusive data on the therapeutic potential of combining CEFID with other antibiotics [ 60 ].…”
Section: Recently Approved Antimicrobial Agentsmentioning
confidence: 99%
“…The high prevalence of heteroresistance to CFD has been proposed as an explanation for the suboptimal efficacy of CFD against carbapenem-resistant bacteria, particularly A. baumannii [ 86 , 87 ]. However, an increasing number of cases of the in vivo emergence of resistance during treatment have been reported [ 70 , 88 , 89 , 90 ].…”
Section: Disadvantage Of These New Antibiotics?mentioning
confidence: 99%